2013
DOI: 10.7314/apjcp.2013.14.8.4717
|View full text |Cite
|
Sign up to set email alerts
|

An Australian Retrospective Study to Evaluate the Prognostic Role of p53 and eIF4E Cancer Markers in Patients with Head and Neck Squamous Cell Carcinoma (HNSCC): Study Protocol

Abstract: Complete surgical resection of the primary tumour is a crucial predictive step for head and neck squamous cell carcinoma (HNSCC), because incomplete resection may lead to increase in the recurrence rate. Molecular cancer markers have been investigated as potential predictors of prognosis marker, to identify patients who are at high risk of local recurrence. This retrospective study aimed to determine the prognostic correlation between p53 and eIF4E expression and clinical characteristics, recurrence and overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…However, these technologies have had little impact on standard methods for diagnosis and treatment of HNSCC and many other types of cancer with one or more known mutational or copy number drivers. Despite extensive literature of differential gene expression profiles, mutations and copy number abnormalities in head and neck tumors that could potentially impact future clinical applications, little other than HPV status is done routinely upon diagnosis [7,10,11,13,15,24,32,[35][36][37][38][39][40][41][42][43][44][45][46][47]. A main factor contributing to this lack of progress is that no clear directives or actionable guidelines have been adopted for molecularly profiling HNSCCs.…”
Section: Discussionmentioning
confidence: 99%
“…However, these technologies have had little impact on standard methods for diagnosis and treatment of HNSCC and many other types of cancer with one or more known mutational or copy number drivers. Despite extensive literature of differential gene expression profiles, mutations and copy number abnormalities in head and neck tumors that could potentially impact future clinical applications, little other than HPV status is done routinely upon diagnosis [7,10,11,13,15,24,32,[35][36][37][38][39][40][41][42][43][44][45][46][47]. A main factor contributing to this lack of progress is that no clear directives or actionable guidelines have been adopted for molecularly profiling HNSCCs.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study conducted in Darwin suggested the efficacy of IHC with eIF4E and p53 antibodies on surgical margins of HNSCC in assessing the completeness of surgery; however, the sample size was very small for a concrete conclusion. 14 Hence, a larger sample and prospective study was warranted to validate the above finding.…”
Section: Discussionmentioning
confidence: 82%
“…Among the states and territories in Australia, Northern Territory has the highest incidence of HNSCC and the RDH is the largest public hospital that facilitates the treatment and management of the disease. 14 The actual burden of head and neck cancer in India is much greater than that reflected in the existing literature; however, it is the the most common malignancy encountered in Indian males. 15 According to WHO, lip and oral cancers is the third most common cancer in India with nearly 68% mortality in 2012.…”
Section: Discussionmentioning
confidence: 99%
“…eIF4E may have a role as the product of a proto-oncogene and as a tumour marker, and expression of eIF4E may be helpful in predicting prognosis and choosing appropriate therapeutic schedules. 12,13 Since considerable protein synthesis occurs during the development of a solid tumour, expression of eIF4E is likely to be of importance. Overexpression of eIF4E can promote the expression of growth factors and cell growth-regulating factors, which are known to be closely related to tumour formation.…”
Section: Discussionmentioning
confidence: 99%